DNA barcode assessment of Mediterranean mayflies (Ephemeroptera), benchmark data for a regional reference library for rapid biomonitoring of freshwaters. (October 2015) - Cardoni, Simone; Tenchini, Roberta; Ficulle, Irene; Piredda, Roberta; Simeone, Marco Cosimo; Belfiore, Carlo
Abstract: Accurate identification of aquatic species is fundamental to freshwater research. In this paper, we targeted Ephemeroptera, a key taxonomic insect group for biomonitoring of water bodies and present an overview on the efficacy of the DNA barcoding approach to document species identity in the Mediterranean region. We sequenced the mitochondrial cytochrome c oxidase (COI) in 39 nominal species. Sample discrimination and species identification were investigated by evaluating haplotype identity and similarity, intra-/interspecific genetic distances, optimal identification of barcoding gap thresholds, estimates of species monophyly and comparative species matches on available reference libraries. The resolving power of the obtained data was discussed in the light of statistical tools such as Spider R-package and Poisson Tree Processes. High levels of species identification were achieved with all the used methodologies, and the occurrence of cryptic species was suggested. We conclude that DNA barcoding is a powerful tool for taxonomic research in Mediterranean mayflies, with great promise to ameliorate biodiversity inventories of freshwater ecosystems and to provide the necessary accuracy for water quality assessment programs. Our results further indicated we need to upgrade the current regional mayfly diversity knowledge. The development of a Mediterranean reference library could integrate this new information system. Highlights: We performed DNA barcoding of Mediterranean Ephemeroptera, a key taxonomic insect group for biomonitoring of water bodies. The resolving power of DNA barcoding was assessed with statistical tools such as spider R-package and poisson tree processes. High levels of species identification were achieved and the occurrence of cryptic species was suggested. Our results indicated we need to upgrade the current regional mayfly diversity knowledge.